Requiem to Window Sealant - Jaworski, Sophia (UnderCurrents: Journal of Critical Environmental Studies, 2022)
Requiem to Window Sealant is an autobiographical exploration of chemical sensitivity. Rather than framing her experiences explicitly within illness or suffering, the author gestures towards the sensory implications and the co-materiality of life in plastic worlds. The photograph is a multiple exposure of a body filled with a raft of grass, trash, and detritus floating out to Lake Ontario. It was taken at the mouth of the Don River.